THE IMPACT OF PICTORIAL HEALTH WARNINGS ON SMOKING CESSATION INTENTION: A NARRATIVE REVIEW BASED ON THE THEORY OF PLANNED BEHAVIOR - Sandra Reinny Parengkuan; Nur Rohmah; Annisa Nurrachmawati (Mulawarman International Conference on Tropical Public Health, 2025)
Cigarette consumption in Indonesia remains high, underscoring the need for effective tobacco control strategies such as Pictorial Health Warnings (PHWs). This study aims to analyze the influence of PHWs on the components of the Theory of Planned Behavior (TPB)—attitude, subjective norm, and perceived behavioral control—and their subsequent effect on the intention to quit smoking. A systematic Narrative review was conducted using indexed scientific databases, including Scopus, DOAJ, and PubMed, for the period of 2020–2024. The review included three primary studies that met the inclusion criteria and focused on smoking cessation behavior, the TPB framework, and pictorial media as an intervention. The findings consistently demonstrate that graphic visualizations of smoking-related hazards positively influence smokers' attitudes, enhance social awareness (subjective norm), and strengthen perceived behavioral control over quitting. The combination of emotionally compelling imagery and cognitive messaging proved effective in reinforcing quit intentions within the TPB framework. In conclusion, PHWs effectively target the key determinants of behavioral intention outlined in the TPB. An emotionally powerful visual approach significantly boosts smokers' awareness and motivation to quit, affirming the utility of PHWs as a critical public health intervention.